A combined intervention strategy to increase linkage to and retention in substance use treatment for individuals accessing hospital-based services: study protocol - Crisanti, A. S.; Page, K.; Saavedra, J. L.; Kincaid, T.; Caswell, C. M.; Waldorf, V. A. (Frontiers in Psychiatry, 2024)
Background: In 2020, New Mexico had the highest alcohol related death and the 11th highest drug overdose rate in the U.S. Towards the long-term goal of addressing this public health problem, we are implementing and evaluating an multi-level intervention designed to identify adults at risk of substance use disorder (SUD) and encourage linkage to and retention in treatment. The first level includes equipping the ED and medical inpatient units of a safety-net hospital with a method to screen individuals at risk of a SUD. The second level includes Seeking Safety (SS), a trauma-specific treatment for PTSD and SUD; and pharmacotherapy for SUD. Motivational Interviewing (MI) is used throughout both levels. Using the SPIRIT guidelines and checklist, this study protocol describes the multi-level intervention and the methodology we are using to assess feasibility and effectiveness. Methods: We are using a Type 1 hybrid implementation design with a non-randomized approach (ISRCTN registration # ISRCTN33100750). We aim to enroll 110 adults (≧18) who screen positive for unhealthy use of alcohol, prescription medications (used nonmedically) and/or illicit drugs. Peer support workers are responsible for screening, using MI to increase engagement in screening and treatment and delivery of SS. Pharmacotherapy is provided by addiction clinical specialists. Treatment is provided post hospital discharge via telehealth to increase access to care. Participants are identified through (1) review of electronic health records for individuals with a chief or secondary complaint or mental health condition relating to alcohol and/or other drug use, (2) referrals from clinical staff and (3) screening in the ED and medical inpatient units. Feasibility is being measured through process data. Effectiveness will be determined by changes in two primary outcomes: (i) PTSD symptom severity; and (ii) substance use. Discussion: Our study will expand on research related to the implementation of treatment strategies for patients presenting at EDs and admitted to medical inpatients units wherein there is a significant window of opportunity to link patients with follow-up behavioral and clinical services for alcohol and/or drug misuse. The challenges associated with implementation and strategies that have been helpful to address these challenges will further inform the field.